Translating a subset of english to defeasible logic programs - García, Alejandro Javier (2000)
Defeasible Logic Programming (DeLP) is an extension of Logic Programming capturing common-sense reasoning features. The DeLP language can manage defeasible reasoning, allowing the representation of defeasible and non- defeasible knowledge. Since DeLP syntax is based on a PROLOG-like notation, the task of writing a DeLP program is similar to that of writing a Prolog one. Hence, writing a DeLP program could be hard for someone unfamiliar with this kind of syntax. In this paper we present a window-based system that assists a user in the writing of DeLP programs. The system allows the user lo write sentences in restricted English and then translates these sentences to DeLP syntax. The system is strongly based on a natural language interpretation module for translating a subset of English to DeLP. The translator has the capability of learning new words directly from the sentences being parsed. Thus, the system lexicon is built dynamically while the program is being written. This adaptive feature makes the system usable in any application domain.